Analysis Clustering of the Global Pandemic Covid-19 using K-Means Algorithm - Bakti Siregar; Yosia (Formosa Journal of Applied Sciences, 2023)
A pandemic such as Covid-19 is one of the biggest real problems ever in the world. This case has confirmed how uncertainty affects the global economy. The pandemic Covid-19 cannot be solved by one method over the world, it depends on the severity of the case. Therefore, this research aims to cluster the severity of Covid-19 using the K-means algorithm to reflect the global economic conditions using data sources from "Our World in Data". The results of this research can be used as materials to overcome the impact of the global pandemic by referring to policies and strategies from a country that is indicated in one cluster.